1994
DOI: 10.1084/jem.179.3.889
|View full text |Cite
|
Sign up to set email alerts
|

Identification of membrane-bound CR1 (CD35) in human urine: evidence for its release by glomerular podocytes.

Abstract: SummaryComplement receptor 1 (CR1) is present on erythrocytes (E-CR1), various leucocytes, and renal glomerular epithelial cells (podocytes). In addition, plasma contains a soluble form of CR1 (sCR1) By using a specific ELISA, CR1 was detected in the urine (uCR1) of normal individuals (excretion rate in 12 subjects, 3.12 + 1.15 #g/24 h). Contrary to sCR1, uCR1 was pelleted by centrifugation at 200,000 g for 60 min. Analysis by sucrose density gradient ultracentrifugation showed that uCR1 was sedimenting in fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(61 citation statements)
references
References 47 publications
1
60
0
Order By: Relevance
“…It is also expressed in renal glomerular podocytes [2]. CR1 binds C3b-coated particles and serves as a cofactor for the degradation of C3b by factor I.…”
Section: Introductionmentioning
confidence: 99%
“…It is also expressed in renal glomerular podocytes [2]. CR1 binds C3b-coated particles and serves as a cofactor for the degradation of C3b by factor I.…”
Section: Introductionmentioning
confidence: 99%
“…Characteristics of SF CR1 compared with other forms of CR1. Previous experiments have shown that serum sCRl is not pelleted by ultracentrifugation for 60 minutes at 200,OOOg (5). By contrast, all urinary CR1, which is known to be a transmembrane molecule on urinary vesicles, is pelleted.…”
Section: Resultsmentioning
confidence: 94%
“…Thus, the cellular release of CR1 in vivo may occur via 2 different mechanisms, enzymatic cleavage (ie., shedding of the extracellular portion of the molecule) and cellular microvesiculation (5,6). PMN that invade the synovium in patients with inflammatory joint conditions resemble in vitroactivated cells (9), which are known to release a soluble form of CR1.…”
Section: Cr1 Cd35 In Synovial Fluid From Patients With Inflammatory mentioning
confidence: 99%
“…The size and solubility of sCR1 were assessed by ultracentrifuat 260,000g at room temperature, and 24 fractions of 200 mL were collected from the bottom. 10 The immunoglobulin M position was gation and chromatography studies. First, serum samples from 4 patients with cirrhosis and 2 normal controls were centrifuged at determined using radiolabeled monoclonal immunoglobulin M. sCR1 was measured in the fractions by ELISA as described above.…”
Section: Methodsmentioning
confidence: 99%
“…Data from 3 such patients are presented in liver disease was not aggregated, fragmented, or bound to cell fragments or vesicles released from cells. 10,16 Thus, the Fig. 5.…”
Section: Scr1 In Patients Withmentioning
confidence: 97%